Multiple disc herniation in spondyloepiphyseal dysplasia tarda: A rare case report and review of the literature - Zan Chen; Zheyi Zhang; Fei Ye; Fei Lei; Daxiong Feng (BMC Musculoskeletal Disorders, 2022)
Abstract Background Spondyloepiphyseal dysplasia tarda (SEDT) is a rare, hereditary, X-linked skeletal disorder. To our knowledge, there are few reports about orthopedic surgery in these patients. This is the first report on patients with SEDT undergoing spinal and fracture reduction surgery. Case presentation A 31-year-old male patient who had been misdiagnosed with juvenile idiopathic arthritis (JIA) for 20 years and who had been treated with femoral shaft internal fixation for lower extremity fracture caused by minor trauma presented at hospital with stiffness and weakness in the lower extremities for the past two years. Radiographs showed bony dysplastic features of flattened vertebral bodies, Scheuermann-like changes in the spine, and osteoarthritis-like changes in the joints. Laboratory examination, including routine blood tests and rheumatism-related indicators showed negative results. Considering the history, radiology, and genetic findings, a diagnosis of spondyloepiphyseal dysplasia tarda with progressive arthropathy (SEDT-PA) was considered. Further neurological examination indicated that severe spinal cord compression was an important reason for the patient’s inability to walk. Laminectomy, spinal canal decompression, internal fixation and fusion were performed. Clinical outcome was satisfactory at one-year follow-up. The lower-limb fatigue was relieved, the patient could walk independently, and his examination showed osseous fusion. The English database was searched and the literature was reviewed for the relevant keywords of “SEDT-PA”. Conclusions Progress has been made in genetic research on SEDT; early diagnosis is particularly important, but the clinical diagnosis and treatment plans are still evaluated on a case-by-case basis. The best treatment for SEDT is to identify patients with progressive neurological and joint-mobility impairments and perform appropriate surgical intervention. Surgical intervention can improve neurological function and quality of life. However, surgery, as palliative care, does not alter the progression of the disease.